Effectiveness of Trauma-Focused Psychological Therapies for Treating Post-traumatic Stress Disorder Symptoms in Women Following Childbirth: A Systematic Review and Meta-Analysis - Furuta, Marie; Horsch, Antje; Ng, Edmond S. W.; Bick, Debra; Spain, Debbie; Sin, Jacqueline (Frontiers in Psychiatry, 2018)
Background: Approximately 3% of women in community samples develop posttraumatic stress disorder (PTSD) after childbirth. Higher prevalence rates are reported for high risk samples. Postpartum PTSD can adversely affect women’s wellbeing, mother-infant relationships and child development. This study aims to examine the effectiveness of trauma-focused psychological interventions (TFPT), for postnatal women. Methods: We conducted a systematic review and meta-analysis including all clinical trials which reported post-traumatic stress symptoms for both the intervention and control groups or at least two time-points, pre- and post-intervention. We searched four databases: CENTRAL, MEDLINE, PsycINFO and OpenGrey. Screening of search results, data extraction, and risk of bias assessment were undertaken independently by two reviewers. Results: Eleven studies, reported in 12 papers, involving 2,677 postnatal women were included. All were RCTs, bar one case series. Interventions varied in modality, duration and intensity, and included exposure therapy, trauma-focused cognitive behavioural therapy, eye movement desensitization and reprocessing and other psychological approaches. Participants had experienced uncomplicated births, emergency caesarean sections and / or preterm births. Results suggest that TFPT are effective for reducing PTSD symptoms in the short term (up to three months postpartum [4 RCTs, n = 301, SMD = -0.50, 95% CI = -0.73 to -0.27]), and medium term (i.e. 3-6 months postpartum [2 RCTs, n = 174, SMD = -1.87, 95% CI = -2.60 to -1.13]). However, there is no robust evidence to suggest whether TFPT can also improve women’s recovery from clinically significant PTSD symptoms. Conclusion: Further larger studies, distinguishing between low and high risk groups, and with adequate follow-up, are needed to establish which TFPT are most effective and acceptable for treating postnatal PTSD.